Root K Affinity Drivers and Photosynthetic Characteristics in Response to Low Potassium Stress in K High-Efficiency Vegetable Soybean - Liu, Changkai; Wang, Xue; Tu, Bingjie; Li, Yansheng; Chen, Heng; Zhang, Qiuying; Liu, Xiaobing (Frontiers in Plant Science, 2021)
Significant variations of potassium absorption and utilization exist in vegetable soybean. Pot and hydroponic experiments were carried out to examine the characteristics of root K affinity-associated drivers and photosynthesis in vegetable soybean (edamame) (Glycine max (L.) Merr.) with different K efficiency. Two K high-efficiency vegetable soybean genotypes (Line 19 and Line 20) and two K low-efficiency genotypes (Line 7 and Line 36) were investigated in low K and normal K conditions. The root of K high-efficiency genotypes had a higher K+ affinity associated with higher maximum K+ uptake rate (Imax), but lower Michaelis constant for K+ absorption (Km) and lower compensation concentration for K+ uptake (Cmin). Seedlings of K high-efficiency genotypes also had higher root vigor (TTC reduction method) and greater absorbing activity (methylene blue method), especially in the low K condition. Besides, the root bleeding-sap rate of K high-efficiency genotypes in low K stress was 9.9~24.3% greater than that of normal K conditions, which was accompanied with relatively higher K concentration of root bleeding-sap in contributing to K+ upward flux. The root of K high-efficiency vegetable soybean genotypes exhibits K+ high-affinity and driving advantages. Photosynthetic parameters of K high-efficiency vegetable soybean genotypes were less affected by low K stress. Low K stress decreased the net photosynthetic rate of K high-efficiency genotypes by 6.1~6.9%, while that of K low-efficiency genotypes decreased by 10.9~15.7%. The higher Chl a/b ratio with enhanced relative content of Chl a in response to low K stress might be an adapted mechanism for K high-efficiency genotypes to maintain photosynthetic capacity. Stronger root K affinity drivers associated with photosynthetic adaptability to low potassium stress are the key factors in determining the K high-efficiency of vegetable soybeans.